CONGRUENCY AND ACADEMIC PERFORMANCE: AN ANALYSIS OF THE TEACHING-LEARNING PROCESS - Young, Bertrem (My University, 1971)
This study reviews the relevant research concerning the factors affecting academic performance in post-secondary education and offers a tentative model of the teaching learning process with which to analyze the social and educational factors affecting academic performance. The data employed in the study were collected in April of 1970 via a questionnaire given to the first year students enrol1ed in the introductory course, Sociology 1a6, at McMaster University. The results indicate partial support for the major hypothesis which stated that academic performance and satisfaction varies directly with the degree of congruency existing between the student's input, the instructional input, and the evaluation criteria. The results also showed that high school final grades, midterm grades in sociology, and religion are all significantly related to academic performance. On the basis of the results, a revised teaching-learning model is proposed in the hope that further research will critically test its validity.
Keywords: Anthropology; Sociology; Anthropology